Social systems theory as theoretical framework for Human Resource Management: Benediction or curse? - Wolfgang Mayrhofer (Management Revue, 2004)
Social systems theory as developed by Niklas Luhmann is an option for the theoretical foundation of Human Resource Management (HRM). After clarifying the advantages of using a grand (social) theory as the basic theoretical perspective, the roots of this social systems theory - the deterministic view of systems as machines, the open systems approach and non-linear systems theory - are addressed. Based on the view of social systems as autopoietically closed systems, five major contributions to a theoretical foundation of HRM are identified: (1) the conceptualisation of organising and managing human resources as social processes, thus overcoming an individualistic angle; (2) the new importance of individuals as essential element in the system's environment; (3) the abstention form far reaching or highly unrealistic assumptions about the 'nature' of human beings; (4) the interaction between various levels and units of analysis built into the theory which is essential for comprehensive and in-depth analyses of HR phenomena and (5) the openness for additional theories for which social systems theory provides the overall framework.
Keywords: 650; systems theory; Human Resource Management; organisation theory; Systemtheorie; Personalmanagement; Organisationstheorie